(untitled) (Academia Journal of Medicine, 2020)
Background: This study was done to create awareness among people about the problems of Anemia and health care providers in further management. The aim of this study was to assess the prevalence, severity, risk factors of anemia among 2-12 years of aged children attending a hospital. Subjects and Methods: Blood and stool samples were collected from the patient. Among those children with hemoglobin <11 g/dl, were screened for iron deficiency anemia (serum ferritin estimation is done). Among these 500 children, 100 children with a hemoglobin level of 11gm/dl and serum ferritin <12 μg/l were taken up for detailed study. Results: A total of 138 males 62.7% were having hemoglobin less than 11.4 gm. /dl indicating anemia. total 230 female children about 66.5% were detected with anemia, 73 (31.73%) children had Hemoglobin levels less than 8 gm. /dl indicating severe anemia and about 49 (21.30%) children had moderate anemia and 31 (13.47%) had mild anemia and only 77 (33.47%) were having their hemoglobin concentration of greater than 11.5 gm. /dl were classified as non-anemic. Conclusion: Anemia was slightly more prevalent in girls of the same age group as compared to boys.